Nursing care in the promotion of self-care in patients with intestinal ostomies (Research, Society and Development, 2023)
This study aimed to identify the evidence brought by studies on nursing care for patients with intestinal ostomies. Integrative literature review in which searches were carried out in the LILACS, SciELO, BDENF databases, considering as inclusion criteria articles published in Portuguese, from the year 2017. Studies that did not answer the guiding question. 10 articles were selected, all publications of Brazilian origin. The analysis made it possible to identify three thematic axes, namely: health education for ostomized patients during nursing care, main difficulties encountered by patients in carrying out self-care, the importance of the family role and assured rights. Health education, promoted by the nursing team is of fundamental importance for adaptation, mastery and skills in the development of self-care. It should be noted that nursing conduct and guidelines can improve the understanding and acceptance of this new condition of life among ostomy patients, family members and society, thus reducing the possible negative sequelae that this condition may bring.